Idiopathic Atrophoderma Of Pasini And Pierini Hypertrphic Scar After Punch Biopsy-An Indirect Proof Of Dermal Atrophy - Malakar Subrata; Dhar Sandipan (Wolters Kluwer Medknow Publications, 1998)
Idiopathic atrophoderma of pasini and pierini (IAPP) affects typically persons in second and third decades of life. It is believed that the disorder is characterized by atrophy of dermis. Punch biopsies done in 5 consecutive patients of IAPP showed healing of the biopsy wounds with hypertrophic scare by the end of second week. The consistent finding of hypetrophic scar after punch biopsy in idiopathic atrophoderma of pasini and pierinin indirectly proves the atrophy of the dermis.